2002
DOI: 10.1149/1.1462792
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of Oxygen Reduction on Polypyrrole/Mixed Valence Spinel Oxide Nanoparticles

Abstract: Composite electrodes based on mixed valence oxide nanoparticles ͑Ox͒ embedded in an electrically conductive polymer ͑ECP͒ were investigated toward the oxygen reduction reaction ͑ORR͒. ECP was polypyrrole ͑PPy͒, and Ox was the spinel mixed valence oxide Cu 1.4 Mn 1.6 O 4 , which is known to be an electrocatalyst of the ORR in neutral and alkaline media. The main findings were that in such a composite electrode ͑i͒ the spinel lattice and the electrocatalytic activity of the oxide remained remarkably stable in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In subsequent publications [24][25][26], we have confirmed the feasibility for the ORR of multilayer composite electrodes having the structure GC/ PPy/PPy(Ox)/PPy (GC, glassy carbon; PPy, polypyrrole; Ox, oxide), Ox being a spinel oxide of copper and manganese, Cu 1.4 Mn 1.6 O 4 or nickel and cobalt, Ni 0.3 Co 2.7 O 4 . In the composite electrode, nanoparticles of the electrocatalyst, Ox, were sandwiched between two PPy layers.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…In subsequent publications [24][25][26], we have confirmed the feasibility for the ORR of multilayer composite electrodes having the structure GC/ PPy/PPy(Ox)/PPy (GC, glassy carbon; PPy, polypyrrole; Ox, oxide), Ox being a spinel oxide of copper and manganese, Cu 1.4 Mn 1.6 O 4 or nickel and cobalt, Ni 0.3 Co 2.7 O 4 . In the composite electrode, nanoparticles of the electrocatalyst, Ox, were sandwiched between two PPy layers.…”
Section: Introductionsupporting
confidence: 60%
“…If the same procedures was adopted to prepare the composite electrode as in our previously publications [23][24][25][26], much less quantity of the oxide can be involved in the polymer matrix due to the blocking of CC porous structures by first PPy layer and the very limited solubility of the oxide. In this case, therefore, directly pipetting the oxide dispersion solution onto CC was used as described in the experimental section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, non-PGM cathode catalysis research has focused on three main groups of compounds with particularly good promise: inorganic oxides [4][5][6], metal selenides [7,8], and pyrolyzed N 4 -transition metal macrocycles and N 4 -metal chelates of Fe or Co [9][10][11][12]. Several groups showed that templated CoTMPP-based ORR catalysts, supported on various carbon or silica templates and then heat-treated, are active in oxygen reduction but not methanol oxidation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%